THE CURRENT STATE OF LOGISTICS DEVELOPMENT IN AZERBAIJAN (International Journal of Innovative Technologies in Economy, 2022)
The main purpose of the study is to analyze the current state and level of development of the logistics sector in Azerbaijan. The research was based on research methods such as comparative analysis and logical generalization. The article reflects the ongoing development with the establishment of logistics centers and junctions in the "Strategic Roadmap for the development of logistics and trade in the Republic of Azerbaijan", which began with the signing of the Contract of the Century. As a result of the study, the reasons and indicators of Azerbaijan's transformation into a global logistics hub were noted. The limitations of the study are that it requires more practical information. The practical significance of the study is to emphasize that the establishment of logistics centers will make Azerbaijan a center that can meet the needs of international freight.